INTERNALISASI NILAI-NILAI PENDIDIKAN AGAMA ANAK DALAM KELUARGA - Barkatillah Barkatillah (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2021)
The family as the first educational center is the initial phase, the basis, the foundation that will determine the continuity and success of further education, because education in the family is a natural education center that takes place with full fairness compared to other educational centers. Parents as people who are most responsible for the education of children are obliged to educate their children according to the position that has been given the mandate by God, by nature they are motivated to guide their children to become adult human beings, live a decent life, be religious, become good children. pious, happy in this world and in the hereafter The role of parents in educating children through proper religious education from an early age is very important, even mental religious development for children begins from the time of conception, this is in accordance with the concept of psychology and Islamic teachings which state that mental conditions A mother who is pregnant will affect the mentality of the child in the future. Religious values ​​have a very big influence on family success, religion instilled by parents from a young age will have a big impact in adulthood, because the religious values ​​given reflect self-discipline with religious nuances Internal education of children's religion in the family can be done through faith education, moral education, physical education, intellectual education, psychological education, social education, and sexual education. Religious education in the family environment begins to be instilled since marriage even when choosing a mate, because it is the initial formation of the family. . In this marriage bond, it is hoped that peace and tranquility will be created in human life. Finally, it is hoped that every family will realize that the internalization of the values ​​of religious education in children is the most important part in preparing superior children.